Effects Of Moisture On Acrylonitrile Butadiene Styrene (Abs) Filament Material In Fused Deposition Modeling (Fdm) Rapid Prototyping Machine - Halidi, Siti Nur Amalina Mohd (2013)
Acrylonitrile butadiene styrene (ABS) is a type of thermoplastic that becomes brittle after a few months or even weeks, when left outdoors. Due to its hygroscopic nature, this material gradually degrades and becomes unsuitable for use in Fused Deposition Modeling (FDM). In this work, a study on the effects of moisture in ABS properties is conducted. Experiments were conducted such that filaments were exposed to different types of humidity conditions for a certain amount of time. Experimental test on the effect of moisture on physical, thermo mechanical, rheological, and chemical structure changes were observed. The filaments’ diameter and weight changes are measured to assess the ABS’s suitability for use in FDM liquefier. Weight difference measurement was done to observe the material’s moisture sorption ability. After being exposed for a certain amount of time, the ABS filament diameter increased up to 3.93% (for ambient condition) and 1.86% (for desiccated environment) from its as-received diameter. Using DSC, thermo-mechanical behavior, in terms of glass transition temperature (Tg) was found to decrease over time in all environmental conditions. Raw data curve shifted to the left indicates a decrease in Tg. FTIR analysis was done to observe the presence of OH bond with moisture absorption by the filament. O-H bond exists with moisture absorption as shown in region 3600-3200 cm-1. Capillary rheometer was used to observed melt flow behavior. ABS filament exposed to wet condition showed the highest viscosity (ranged between 52.6 to 258 Pa•s) while ABS filament exposed to dry condition showed the lowest viscosity (ranged between 49.65 to 212 Pa•s). Based on simulations on FLUENT, temperature profiles remained constant throughout the liquefier. Viscosity decreases as with increase of shear stress, agreeing to the data from rheometry experiment. In summary, moisture causes degradation of ABS to the extent that it becomes unfit for use in RP due to decrease in thermal and rheological properties.